The concept of personality in axiological psychology: contours of the essential heuristics - Furman, Anatoliy A. (Psyhology & society, 2019)
The article is devoted to meta-theoretical analysis of the conceptual plan-card of personality that is substantiated in the axiological psychology and in its central link is connected with thorough writings of the founder of this new direction of psychological science professor Zinovii Karpenko. As a result of theoretical reflection of axiogenesis of personality as a holistic process of establishing value-semantic sphere into complementarity of ontophenomenological dimensions, forms and priorities of filling the semantic meaning, levels of potentiation and functioning, stages, ingredients, components and parameters of development its value consciousness. It is proved that the core of personal self-cognition and self-creation is a deed which in the full expression is always appears as an act of spiritual development of the personality and as a process of actualization its moral values. Application of the system, hermeneutic and sphere approaches enabled semantic single out of emotional-sensual, cognitive, needs-motivational, actively-willed spheres in the global axiosphere of personality and also enabled to describe eight level cycle of its formation as a value-oriented psychospiritual givens that broadly confirms heuristic of axio-psychological approach in the modern humanitarian discourse.